2015
DOI: 10.1089/thy.2015.0170
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Patients with Metastatic Carcinoma Treated with Sunitinib: Is Thyroid Autoimmunity Involved?

Abstract: These data confirm the thyroid inhibitory effect of sunitinib, in keeping with the key role of kinases in controlling thyroid function and growth. However, the novel appearance of TPOAb in a subgroup of patients with more severe hypothyroidism and longer survival indicates that sunitinib may also trigger/exacerbate thyroid autoimmunity contributing to thyroid failure. The development of TPOAb was associated with a longer PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…First, the follow-up period was only 24 weeks, and therefore we cannot exclude the possibility that the patients who had positive antithyroid Abs but not thyroid dysfunction during the observation period will develop destructive thyroiditis or hypothyroidism in the future. Indeed, a previous study suggested that long-term observations are necessary to clarify the role of autoimmune mechanisms underlying hypothyroidism development in patients treated with sunitinib [ 26 ]. However, it has been reported that most nivolumab-induced adverse events occurred within the first 16 weeks of treatment [ 9 ] and that irAEs in the thyroid mostly developed within the first 3 months [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the follow-up period was only 24 weeks, and therefore we cannot exclude the possibility that the patients who had positive antithyroid Abs but not thyroid dysfunction during the observation period will develop destructive thyroiditis or hypothyroidism in the future. Indeed, a previous study suggested that long-term observations are necessary to clarify the role of autoimmune mechanisms underlying hypothyroidism development in patients treated with sunitinib [ 26 ]. However, it has been reported that most nivolumab-induced adverse events occurred within the first 16 weeks of treatment [ 9 ] and that irAEs in the thyroid mostly developed within the first 3 months [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this view also thyroid dysfunction has been evaluated in patients treated with sunitinib. In renal cell carcinoma patients receiving sunitinib the development of antithyroid peroxidase (TPOAb) autoantibodies along with severe hypothyroidism was associated with a longer progression free survival (PFS)16. In the TRIBUTE (Toxicity during Regorafenib Induction and Benefit Under Treatment Extension) analysis we evaluated the potential role of off target effects as early surrogate markers of clinical outcome in patients with colorectal cancer treated with regorafenib with the final aim to improve the early identification of patients more likely to benefit from such a treatment approach and optimise adverse events management.…”
mentioning
confidence: 99%
“…13 Several mechanisms may play a role in TKI-induced hypothyroidism including decreased thyroid gland capillary density, induction of type 3 deiodinase activity, inhibition of iodine uptake, inhibition of peroxidase activity, altered thyroid hormone transport, decreased thyroid hormone synthesis, and in some patients, thyroid autoimmunity resulting in thyroid failure. [14][15][16][17][18] Studies performed in rats exposed to sunitinib showed changes in thyroid gland capillary density, which was both structural and functional in nature. These changes were hypothesized to be caused by the antiangiogenic effects of vascular endothelial growth factor (VEGF) receptor inhibition and increased concentrations of circulating endothelin-1.…”
mentioning
confidence: 99%